Exploring the perception of and attitude towards preconception care service provision and utilisation in a South Western Nigerian community – a qualitative study - Ojifinni, Oludoyinmola O.; Munyewende, Pascalia O.; Ibisomi, Latifat (School of Public Health, University of the Witwatersrand, Johannesburg, South Africa, 2021)
Background: Hospital-based, quantitative studies in Nigeria show low levels of knowledge and use of preconception care (PCC) services. This study explored the perception of and attitude towards PCC in a southwestern Nigerian community qualitatively. Data Source and Methods: Focus group discussions (FGDs) were held with 57 purposively selected adult women and men and key informant interviews (KIIs) with one female and one male community leader in Ibadan North Local Government Area, Oyo State, Nigeria in 2018. The FGDs and KIIs held within the community were digitally recorded, transcribed verbatim and analysed thematically. Results: Participants placed PCC in the context of marriage, describing its importance for addressing effects of adverse exposures on pregnancy and ensuring positive pregnancy outcomes. Conclusion: Barriers to PCC uptake mentioned included lack of awareness and prohibitive service costs. Expressing their willingness to use and promote PCC use, they stated the need to ensure PCC uptake through improved awareness at the community level.
This work is licensed under a Creative Commons Attribution-ShareAlike 4.0 International (CC BY-SA 4.0).
Keywords: Preconception care services; community attitudes to preconception care; context of preconception care; barriers to preconception care